Pengaruh Dosis Pupuk Organik Kompos dan Phonska Terhadap Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.): Effect of Organic Fertilizer Doses Compost and Phonska on The Growth and Production of Cucumber Plants (Cucumis sativus L.) - Lody Bintang Extrada; Supriyono Supriyono; Samudi Samudi (Agrocentrum, 2023)
Cucumber (Cucumis sativus L.) is a type of vegetable from the cucurbit family (Cucurbitaceae) that is already popular all over the world. According to history, cucumber plants originated on the Asian continent. Some sources mention the area of origin of cucumber crops is North Asia. This research has been carried out from January to March 2022 at the Green ccHouse located in Slumbung Hamlet RT. 02 / RW. 22 Village. Slumbung Kec. Ngadiluwih Kab. Kediri. The type of soil in this place is sandy loam.This study used a complete randomized design (RAL) with 2 factors. Factor 1 is the influence of the dose of compost from 3 levels and factor 2 is the influence of the dose of phonska fertilizer from 3 levels so that 9 treatments are repeated 3 times, Factor I. Dose of compost organic fertilizer consists of 3 levels, namely: K1 = 5 tons / Ha, K2 = 10 tons / Ha, K3 = 15 tons / Ha, Factor II. The dose of NPK phonska fertilizer consists of 3 levels, namely: P1 = 100 gr / Ha, P2 = 200 gr Ha, P3 = 300 gr / Ha . The observational data were analyzed using a variance analysis (F test) at a level of 5%. If there is an interaction, it is continued with the 5% BNT test, to find out the difference between treatments. The results showed that the combination of treatment of compost doses and doses of NPK phonka fertilizer showed a noticeable difference in plant height, number of fruits and fruit weight in cucumber plants. In a single treatment, the dose of compost did not show any effect on all observation variables. However, the K1 treatment at a dose of 180 gr / plant became the optimal treatment on the variables of the number of leaves stem diameter, fruit weight, and fruit length. However, in the variable plant height and the number of fruits the best treatment in K2 at a dose of 360 gr / plant. The second factor in the treatment of doses of NPK phonska fertilizer has no influence on the growth and yield of cucumber plants. However, in mite treatment such as npk dose phoska P2 with a dose of 7.2gr / plant became the optimal treatment in this study on plant growth variables that followed the length of the plant, the number of leaves and the diameter of the stem. Meanwhile, the yield variables which include the number of fruits, fruit weight and fruit length of the NPK phonska treatment at a dose of 10.8gr / plant is the best treatment.